The anatomy of peace : resolving the heart of conflict - Berrett-Koehler Publishers; Arbinger Institute (San Francisco, CA : Berrett-Koehler Publishers, Inc., 2008)
Proposes an effective and timely solution to the potentially devastating problem of conflict and its resulting bitterness and regret, contending that only through developing an understanding of ourselves can we confront external conflicts to achieve realpeace.
Through an intriguing story of parents struggling with their troubled children and with their own personal problems, "The Anatomy of Peace" shows how to get past the preconceived ideas and self-justifying reactions that keep us from seeing the world clearly and dealing with it effectively.--Pub. desc.
The heart of peace -- From peace to war -- From war to peace -- Spreading peace.
Originally published: 2006.
Includes index.
Keywords: Conflict management; Interpersonal conflict; Peace -- Psychological aspects